The motive of the mask in the story «Iryi» V. Drozd - Гладкова, Марина Валеріївна; Головко, Людмила Григорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article analyzes the ways of realizing the specificity of the artistic embodiment of the mask’s motive in the novel «Iryi» by V. Drozd, which has an important conceptual value in the artistic system of the work. It is noted that in order to deepen understanding of the motive of a mask in the writer’s work, the author uses an artistic method of comparison, comparing the presentation of the «mask» model of behavior: acting as a professional activity and forms of social hypocrisy. The problem of the organic nature of the coexistence of the human being and the mask is expressed in the work with the help of the symbolic image of the boundary separating the person from the society or, conversely, helping to «enter» it, shaking the boundaries of identity, the eternal opposition of familiar / unfamiliar. It is shown that the auto-textual motive of a mask in the work is used in figurative meaning and has different functional load: it is an means of characterizing characters, amplifying the plot dynamics, revealing the connection with the mythical poetic tradition, ect.